Experimental and theoretical studies of aeroacoustics damping performance of a bias-flow perforated orifice - Zhao, Dan (2021)
Aeroacoustics damping performance of an in-duct perforated orifice with a bias flow in terms of acoustic power absorption Δ and reflection χ coefficients are evaluated in this work. For this, experimental measurements of a cold-flow pipe system with a diameter of 2b with an in-duct perforated plate implemented are conducted over the frequency range of 100 to 1000 Hz first. The effects of (1) the downstream pipe length Ld, (2) porosity η, (3) bias flow Mach number Ma and (4) the orifice thickness lw are experimentally evaluated on affecting the noise damping performance of the in-duct perforated orifice. It is found that decreasing Ld leads to increased Δmax (maximum power absorption). However, the orifice thickness plays a negligible effect at lower frequency, and a non-negligible role at higher frequency range. The maximum power absorption Δmax and reflection coefficients χmax are found to be approximately 80% and 90% respectively. There is an optimum porosity or Mach number corresponding to Δmax. In addition, Δ and χ are periodically changed with the forcing frequency. To simulate the experiments and gain insights on the damping performance of the orifice with a diameter of 2a, an 1D theoretical model that embodies vorticity-involved noise absorption mechanism is developed. It is based on the modified form of the Cummings equation describing unsteady flow through an orifice and the Cargill equation describing acoustically open boundary condition at the end of the downstream duct. It is shown that Δ and χ are strongly related to (1) the bias flow Mach number Ma, (2) forcing frequency ω, (3) porosity η, (4) and the downstream pipe length Ld. Comparing with the experimental measurements reveals that good agreement is obtained. This confirms that the present experimental and theoretical study shed lights on the optimum design of in-duct orifices.